Studi Empiris Nilai Perusahaan Pada Masa Pandemi Coronavirus Disease - Siti Jubaedah; Mardi Mardi; Yudi Aryanto; Otto Fajarianto (Jurnal Akuntansi dan Pajak, 2022)
Corona Virus Disease, which was originally a health problem, had an impact on economic and business activities, affecting the financial sector, one of which is the capital market. So the company must make efforts that are strategic enough to be able to face and get out of financial problems, and maintain the price book value. This study aims to examine the effect of Return On Equity, Debt to Equity Ratio, Dividend Payout Rasio and Managerial Ownership on the price book value. listed on the IDX30 index for the 2016-2020 period. This study used 9 samples using porposive sampling. The type of research used was basic research. The analysis that will be used in this study is multiple regression analysis, classical assumption test, hypothesis testing using t test (partial) and coefficient of determination using SPSS version 25. The results of this study indicate that Return On Equity and Managerial Ownership has a significant effect on firm value while Debt to Equity Ratio and Dividend Payout Ratio have no effect on firm value.